Evaluación del escalamiento de la producción de Polihidroxialcanoatos (pha) por fermentación a partir de la bacteria mutante burkholderia cepacia b27 a nivel semi-industrial (2017)
The low synthetic polymers degradability creates the need to replace them with biopolymers, such as Polyhydroxyalkanoates (PHA) that possess physicochemical properties similar to conventional plastics, but present high production costs. The PHA biosynthesis is an aerobic process and as the scaling criterion the volumetric mass transfer coefficient (KLa) is stable; therefore, a hydrodynamic study of the fermentation was carried out with a model based on a central composite design (CCD).